(Freedom from dependency among students of the Department of Psychological Counseling and Educational Guidance) (build and apply) (Journal of the College of Basic Education, 2022)
The human being seeks freedom, as it is a basic requirement that allows the individual to make his decision and determine his choice from several alternatives without external pressure or redress. And societal, and this requires educators to raise their children to be free from dependence in accordance with the prevailing standards, values ​​and ethics of society.Search objective:1- Building a scale of freedom from dependence among students of the Department of Psychological Counseling and Educational Guidance.2- Identifying freedom from dependence among students of the Department of Psychological Counseling and Educational Guidance. The researcher built a measure of freedom from dependency, which consists of (36) items, using the verbal attitudes method with a triple gradation, extracting the psychometric properties represented by honesty (discriminatory strength, internal homogeneity and stability by re-test method, the (Alpha-Cronbach) equation and the statistical indicators of the scale, and verifying the second objective using T-test for one sample.The research reached the following results:Students of the Department of Psychological Counseling and Educational Guidance enjoy a high level of freedom from dependence.To complement the current research, the researcher presented a number of recommendations and suggestions.